Optimization for maximizing the impact-resistance of patch repaired CFRP laminates using a surrogate-based model. (15th April 2020) - Tie, Ying; Hou, Yuliang; Li, Cheng; Meng, Liang; Sapanathan, Thaneshan; Rachik, Mohamed
Highlights: Numerical method is used to identify the CFRP patch design for low-velocity impact. A surrogate-based optimization is implemented to find optimum design parameters. Surrogate models are built using Diffuse Approximation and design of experiments. The optimum patch designs enhance the impact-resistance of repaired CFRP laminates. Robustness of the optimization protocol is confirmed via various parameter analyses. Graphical abstract: Abstract: This study proposes a surrogate-based optimization model of the external patch design for damaged carbon fiber reinforced polymer (CFRP) laminates to improve the impact-resistance. Initially, finite element (FE) models of patch-repaired CFRP laminates constructed using continuum damage mechanics (CDM) approach and cohesive zone model (CZM), those well capture the intra- and inter-laminar damages during the low-velocity impacts, respectively. Experimental measurements of low-velocity impact tests concur with the numerical predictions and validate the FE models. Subsequently, the validated models are used to optimize the design parameters of repair patch, consisting of patch radius, thickness and off-axis angle. The optimum design parameters are identified using the surrogate models which are constructed using Diffuse Approximation and Design of Experiments (DOE). The identified optimum patch configurations significantly enhance the impact-resistance of repaired CFRP laminates by decreasing the impact energy absorption and the delamination surface area. Finally, the robustness of the optimization model is confirmed via error analysis of surrogate model reconstruction, and testing the influence of polynomial basis and weighting functions.